Compliance among North Indian Celiac Children to Gluten Free Diet. (1st April 2016) - Chishty, Sadia; Monika,; Singh, Nimali
Abstract: Gluten free diet is the only treatment for healing and recovery of mucosa and normalization of symptoms in celiac disease. To study the compliance rate for gluten free diet and consumption of gluten containing items among confirmed Celiac disease patients. Celiac disease patient (7-12 years) previously diagnosed were selected. An interview schedule was developed and pre-tested on 10 percent of sample, then used for data collection by a skilled dietician. Compliance information was derived on the basis of: 1.) 45 gluten containing items 2.) Two day 24 hour dietary recall 3.) Children receiving pocket money. The compliance rate was poor in both the age groups. The mean compliance score was comparatively more in children (7-9 years) than pre-adolescents. Relationship between pocket money receivers and non-compliance was found highly significant (Chi-square value=100.64 at p < 0.01). Compliance rate between both the age groups (that is, 7-9 and 10-12 years) was very poor. Preadolescents are more prone to noncompliance. There is positive impact of knowledge and regular follow up on strict adherence to GFD.